2018
DOI: 10.1038/s41426-018-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the VITEK MS knowledge base version 3.0 for the identification of clinically relevant Mycobacterium species

Abstract: Different Mycobacterium spp. infections may indicate varied treatment regimens in the clinic. Thus, the species-level identification of Mycobacterium spp. is one of the most important tasks for a clinical microbiology laboratory. Although matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) has emerged as a rapid and accurate method for the identification of mycobacteria, this method lacks a comprehensive evaluation of the identification accuracy for clinically collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…In a similar study performed by Luo et al on the evaluation of VITEK R MS version 3.0 for NTM identification, 425/507 (83.8%) isolates were identified the first time, 51/507 (11.24%) additional isolates were identified on repeat, 23/507 (4.53%) isolates remained unidentified and 8/507 (1.6%) isolates were misidentified at species level. Among slowly growing NTM, only 2 out of 56 (3.6%) M. avium and 3 out of 153 (2%) M. intracellulare were unidentified, which was marginally better than the findings in this study [8]. The concordance of 77.5% between VITEK R MS and 16S rRNA sequencing in the identification of slowly growing Mycobacteria is predominantly due to the fact that MALDI-TOF requires moderate growth to be present on the solid media for identification, rather than the scant growth required for sequencing, as demonstrated by other studies as well [37].…”
Section: Maldi-tof Ms and Ntm Species Identificationcontrasting
confidence: 91%
See 1 more Smart Citation
“…In a similar study performed by Luo et al on the evaluation of VITEK R MS version 3.0 for NTM identification, 425/507 (83.8%) isolates were identified the first time, 51/507 (11.24%) additional isolates were identified on repeat, 23/507 (4.53%) isolates remained unidentified and 8/507 (1.6%) isolates were misidentified at species level. Among slowly growing NTM, only 2 out of 56 (3.6%) M. avium and 3 out of 153 (2%) M. intracellulare were unidentified, which was marginally better than the findings in this study [8]. The concordance of 77.5% between VITEK R MS and 16S rRNA sequencing in the identification of slowly growing Mycobacteria is predominantly due to the fact that MALDI-TOF requires moderate growth to be present on the solid media for identification, rather than the scant growth required for sequencing, as demonstrated by other studies as well [37].…”
Section: Maldi-tof Ms and Ntm Species Identificationcontrasting
confidence: 91%
“…The two MALDI-TOF mass spectrometry (MS) platforms, namely VITEK ® MS (bioMérieux, Marcy-l'Étoile, France) and Bruker Daltonics platform (Bremen, Germany) for NTM identification, have been evaluated to identify NTM from both solid and liquid media. VITEK ® MS is a rapid, cost effective and reliable platform, which has the capability to identify as many as 24 NTM species [ 7 , 8 ]. This technology is designed to provide a protein ‘fingerprint’ based on the desorbed ions from cell surfaces by measuring their mass-to-charge ratio.…”
Section: Species Identification Of Ntmmentioning
confidence: 99%
“…The development of several extraction methods enhances the number of bacterial proteins available for MALDI-TOF MS identification. With the increasing amount of mycobacteria data available in commercial databases, MALDI-TOF MS technology has been implemented for NTM identification in many laboratories [ 8 , 19 ]. Several studies have demonstrated that this method can achieve more than 95% agreement with results from DNA sequencing of variable genomic regions (including the 16S rRNA, hsp65 , rpoB , and ITS genes) [ 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory diagnosis methods used for identi cation of mycobacterial species have evolved over the decades [18]. With the development of several extraction methods that enhance the amount of bacterial proteins available for MALDI-TOF MS identi cation, and the increasing amount of mycobacteria data available in commercial databases, MALDI-TOF MS technology has been implemented for NTM identi cation in many laboratories [8,19]. Several studies have demonstrated that this method can achieve more than 95% agreement with results from DNA sequencing of variable genomic regions (including the 16S rRNA, hsp65, rpoB, and ITS genes) [5,20].…”
Section: Discussionmentioning
confidence: 99%